International Influences on Nonviolent and Violent Contention. Issue 4 (4th July 2019) - Breslawski, Jori; Cunningham, David E.
ABSTRACT: How do international actors influence dissidents' decisions whether to challenge their states using violent means, nonviolence, both or neither? We argue that the presence of important actors affects dissident decisions to engage in violent or nonviolent contention by affecting whether dissidents expect that governments will repress or concede to dissident demands in response to this contention. We examine the effect of two prominent types of actors – powerful states with close ties to the government and Highly Structured Inter-Governmental Organizations (HSIGOs) on dissident behavior in all national-level elections in Africa from 2000–2012. Using integrated data drawn from four leading conflict events datasets, we find that dissidents are less likely to engage in violent contention when their government receives higher levels of military aid from the United States and in former French colonies, and more likely to engage in both violent and nonviolent contention when their state is a member of a greater number of HSIGOs.